2022
DOI: 10.1111/1541-4337.12955
|View full text |Cite
|
Sign up to set email alerts
|

Resistant starch—An accessible fiber ingredient acceptable to the Western palate

Abstract: Dietary fiber intakes in Western societies are concerningly low and do not reflect global recommended dietary fiber intakes for chronic disease prevention. Resistant starch (RS) is a fermentable dietary fiber that has attracted research interest. As an isolated ingredient, its fine particle size, relatively bland flavor, and white appearance may offer an appealing fiber source to the Western palate, accustomed to highly refined, processed grains. This review aims to provide a comprehensive insight into the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 100 publications
(230 reference statements)
1
23
0
1
Order By: Relevance
“…33 Specifically, SCFAs tend to have positive effects on human health, e.g., reducing inflammation, decreasing colon cancer, modulating the immune system, and maintaining the integrity of the epithelial barrier. 35 By feeding the C57BL/6NCr mice with RS (as in cooked rice), the production of SCFAs was significantly positively correlated with Bacteroides (a main genus in Bacteroidaceae) and an unclassified genus in S24-7. 33 It thus suggests that the consumption of RS from cooked rice could have physiological significance via modulating the gut microbiome and SCFA production.…”
Section: Rs Production In Whole Rice and Its Observational Effects On...mentioning
confidence: 97%
See 1 more Smart Citation
“…33 Specifically, SCFAs tend to have positive effects on human health, e.g., reducing inflammation, decreasing colon cancer, modulating the immune system, and maintaining the integrity of the epithelial barrier. 35 By feeding the C57BL/6NCr mice with RS (as in cooked rice), the production of SCFAs was significantly positively correlated with Bacteroides (a main genus in Bacteroidaceae) and an unclassified genus in S24-7. 33 It thus suggests that the consumption of RS from cooked rice could have physiological significance via modulating the gut microbiome and SCFA production.…”
Section: Rs Production In Whole Rice and Its Observational Effects On...mentioning
confidence: 97%
“…It was shown that these RSs can reduce the richness and diversity of intestinal microbiota, decrease the Firmicutes/Bacteroidetes ratio, increase the abundance of S24-7 and Bacteroidaceae, and enrich gene families of glycosidases as well as functional pathways related to glycan and carbohydrate metabolism. , The increase of the SCFA production (including acetate, propionate, and butyrate) related to the rice RS consumption is of particular interest . Specifically, SCFAs tend to have positive effects on human health, e.g., reducing inflammation, decreasing colon cancer, modulating the immune system, and maintaining the integrity of the epithelial barrier . By feeding the C57BL/6NCr mice with RS (as in cooked rice), the production of SCFAs was significantly positively correlated with Bacteroides (a main genus in Bacteroidaceae) and an unclassified genus in S24-7 .…”
Section: Rs Production In Whole Rice and Its Observational Effects On...mentioning
confidence: 99%
“…186 The RS is further divided into five different types: physically inaccessible starch (RS type-1), resistant granules (RS type-2), retrograded starch (RS type-3), chemically modified starch (RS type-4), and starch-lipid complex (RS type-5). 187 Although, the RS5 has been traditionally accepted as a V-type complex of starch-lipid complexes, 188 however, recently the complexes of starch with proteins, polysaccharides, glycerol, amino acids, and polyphenols have also contributed to the resistant starch. These self-assembled V-type complexes are recognized as RS5, but further investigation is still needed for the inclusion of SP V-type complexes in the RS5 category.…”
Section: In Vitro Digestibilitymentioning
confidence: 99%
“…El almidón resistente forma parte de la fibra dietaria (Walsh et al, 2022). Ambas formas de almidón, digestible y resistente, contribuyen en el aporte energético en cerdos, o bien como glucosa absorbida o como AGV absorbidos (Fouhse & Zijlstra, 2018).…”
Section: Digestión Del Almidónunclassified